Perlindungan Hukum Terhadap Pengguna Jasa Angkutan Udara Akibat Keterlambatan Penerbangan - Wahid Yaurwarin; Dominggus J. Siwabessy (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
Flight delays are a common problem that air transport service users in our homeland have complained about so far, hence the existence of Law Number 8 of 1999 concerning Consumer Protection, Law Number 1 of 2009, and Minister of Transportation Regulation Number 77 of 2011 concerning Responsibilities. Air Transportation Carrier's Answer is a form of legal protection for the community provided by the state to citizens, especially people who normally use air transportation, the purpose of this article is how to provide legal protection for users of air transport services due to flight delays. The method used is a normative juridical approach, the type of data in this study is primary legal material in the form of laws and regulations which form the basis for legal protection for users of air transport services due to flight delays. Suggestions or recommendations from this article are; There is continuous supervision of airline owners regarding the departure and arrival schedules of airplanes; The government and parties who have concerns in the field of air transportation, should provide socialization to the publik and airline owners about the existence of rights and obligations that cannot be neglected; The government as a regulator must be firm in giving warnings in the form of sanctions to airline owners who are still caught ignoring their responsibilities.